Portable energy dispersive X-ray fluorescence for metal determination of in natura water samples - Melquiades, Fábio Luiz (2010)
A portable EDXRF equipment was used to perform a qualitative and a quantitative in situ analysis of in natura water. Using this equipment 10 mL of water was directly analyzed. Detection limits, in mg L-1, for Cr, Mn, Fe, Co, Ni, Cu, Zn, Se, Hg and Pb were 12.5, 7.5, 4.9, 2.7, 2.8, 2.1, 1.6, 1.9, 3.4, 3.7, respectively, with deviation around 10%. In real samples, Fe, Zn and Pb were identifi ed. Given the obtained results, the analytical system performance appeared to be promising.